2006
DOI: 10.1098/rsif.2006.0113
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fibre recruitment can respond to the mechanics of the muscle contraction

Abstract: This study investigates the motor unit recruitment patterns between and within muscles of the triceps surae during cycling on a stationary ergometer at a range of pedal speeds and resistances. Muscle activity was measured from the soleus (SOL), medial gastrocnemius (MG) and lateral gastrocnemius (LG) using surface electromyography (EMG) and quantified using wavelet and principal component analysis. Muscle fascicle strain rates were quantified using ultrasonography, and the muscle-tendon unit lengths were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
125
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 52 publications
11
125
1
2
Order By: Relevance
“…Preferential recruitment of faster muscle fibres during rapid contractions has been shown in various animal studies, including humans (Gillespie et al, 1974;Gollnick et al, 1974;Grimby and Hannerz, 1977;Hoffer et al, 1981;Citterio and Agostoni, 1984;Wakeling et al, 2006;Hodson-Tole and Wakeling, 2008a;Lee et al, 2013). It has been suggested that complete inhibition of slow muscle fibres in a muscle with mixed fibre types would provide resistance to whole muscle shortening and therefore be detrimental to power production for very fast contractions (Josephson and Edman, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preferential recruitment of faster muscle fibres during rapid contractions has been shown in various animal studies, including humans (Gillespie et al, 1974;Gollnick et al, 1974;Grimby and Hannerz, 1977;Hoffer et al, 1981;Citterio and Agostoni, 1984;Wakeling et al, 2006;Hodson-Tole and Wakeling, 2008a;Lee et al, 2013). It has been suggested that complete inhibition of slow muscle fibres in a muscle with mixed fibre types would provide resistance to whole muscle shortening and therefore be detrimental to power production for very fast contractions (Josephson and Edman, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Wakeling and colleagues (Wakeling et al, 2002) qualitatively showed the presence of preferential recruitment of faster muscle fibres during the cat paw shake in a single muscle (medial gastrocnemius), but was unable to provide quantitative evidence through statistical methods. In a subsequent study, a statistically significant shift towards preferential recruitment of faster muscle fibres was displayed in the human medial gastrocnemius at high cycle frequencies independent of the muscle fascicle strain (Wakeling et al, 2006); however, this shift was identified in the middle of the bursts of muscle excitation and was correlated with the muscle fibre strain rate. Similar findings were subsequently repeated in the rat (Hodson-Tole and Wakeling, 2008b) and the goat (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as velocity increases, earlier recruitment of high-threshold motor units is necessary. 67 Thus neural factors such as a reduced drive from the supraspinal centres after stroke (reflected in the decrease in motor-unit firing rate 9-11 ) may compound the architectural changes in the muscle, producing force deficits, especially at higher velocities. There is some indication that the velocity of force production is an important component of functional recovery.…”
Section: Force-velocity Relationshipmentioning
confidence: 99%
“…On the other hand, changes in composition of muscle fiber types might be associated with muscle overuse and muscle pathologies [17]. The combined use of wavelet and principal component analysis (PCA) is a promising advanced electromyography (EMG) technique that has been successfully applied in gait [18], running [19], and cycling [20] to show that different muscle fiber types are recruited. The purpose of this study was to determine, using EMG and kinetics, the influence of the propulsion speed on the recruitment of shoulder muscles and fast and slow motor units (MUs) during wheelchair propulsion.…”
Section: Introductionmentioning
confidence: 99%